2005
DOI: 10.1007/bf02893048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin A supplementation on hematopoiesis in children with anemia

Abstract: Fifty children (1-4 years age) presenting with micrecytic hypochromic anemia (hemoglobin less than 10g/dl) were studied in two groups of 25 each. Group I was supplemented with iron (ferrous sulphate 6 mg/kg/d) while group II in addition to iron was also supplemented with vitamin A (5000 IU/d). Hemoglobin concentration was found to be significantly increased after 4 weeks of iron supplementation. Rise in hemoglobin was comparatively more in-group II, as compared to group I, after 8 and 12 weeks. Serum iron was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Reasonable number of Randomized Controlled Trials (RCTs) based on daily or weekly VA Supplementation (VAS) have also concluded likewise [8-12]. However, RCTs based on single high dose VAS concluded equivocally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasonable number of Randomized Controlled Trials (RCTs) based on daily or weekly VA Supplementation (VAS) have also concluded likewise [8-12]. However, RCTs based on single high dose VAS concluded equivocally.…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies witnessed significant association between hemoglobin and various VA status indicators [ 6 ]. Reasonable number of Randomized Controlled Trials (RCTs) based on daily or weekly VA Supplementation (VAS) have also concluded likewise [ 8 - 12 ]. However, RCTs based on single high dose VAS concluded equivocally.…”
Section: Introductionmentioning
confidence: 99%
“…36 Some researchers have suggested that vitamin A plays a role in the metabolism of iron; for this reason, many countries have developed supplementation strategies for both iron and vitamin A to reduce the prevalence of anemia. 41 Although the exact interaction of iron and vitamin A is not well known, 23,40 several mechanisms have been suggested, including the regulation of either hematopoiesis 19,24 or various proteins related to iron homeostasis (for example, transferrin, 26 iron regulatory protein 2, 23 and hepcidin). 6,13,15 We conducted this study based on the hypothesis that both vitamin A and iron must be taken together to ensure adequate weight gain and hematologic parameters.…”
mentioning
confidence: 99%
“…Effect of iron deficiency anemia on lipid peroxidation and antioxidant systems increased levels of free radicals in plasma and RBC of IDA patients 1,25,28. Previous studies also reported increased amount of lipid peroxidation by products in the erythrocytes and plasma 29,30 ,31. TBARS remained high as well as antioxidant enzymes.…”
mentioning
confidence: 83%
“…It is a particularly common disorder among infants, preschool-aged children, young women and older people, but it can occur at all ages and in any region. A high demand for iron during rapid growth, pregnancy and lactation, accompanied by dietary deficiencies and menstrual blood loss, are the most common causes of iron deficiency in children, young women and elderly population [28][29][30]. It affects one's development, growth and resistance to infections, and is associated with mortality among children younger than two years old 33.…”
mentioning
confidence: 99%